2021
DOI: 10.1002/ps.6396
|View full text |Cite
|
Sign up to set email alerts
|

Selective actions of insecticides on desensitizing and non‐desensitizing nicotinic acetylcholine receptors in cockroach (Periplaneta americana) neurons

Abstract: BACKGROUND Insect desensitizing nicotinic acetylcholine (nAChD) receptors are desensitized by low concentrations of agonists, including neonicotinoid insecticides, but are essentially insensitive to spinosyns, while non‐desensitizing nicotinic acetylcholine (nAChN) receptors are selectively activated by spinosyns and relatively insensitive to neonicotinoids. RESULTS The single‐electrode voltage‐clamp technique was used to measure the actions of newer nicotinic insecticides dinotefuran, sulfoxaflor, triflumezop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…Electrophysiological studies with native tissues or recombinant receptors showed that low concentrations of neonicotinoids can block nAChR, while higher concentrations can activate the receptor [ 7 , 24 ]. Therefore, it is still unclear whether insecticidal activity is the consequence of nAChR inhibition or activation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies with native tissues or recombinant receptors showed that low concentrations of neonicotinoids can block nAChR, while higher concentrations can activate the receptor [ 7 , 24 ]. Therefore, it is still unclear whether insecticidal activity is the consequence of nAChR inhibition or activation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies with native tissues or recombinant receptors showed that low concentrations of neonicotinoids can block nAChR while higher concentrations cause receptor activation [7,23]. Therefore, it is still unclear whether the insecticidal activity is the consequence of nAChR inhibition or activation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Vincent Salgado gave his award address on nAChRs, an area which he further advances in his research paper detailing the differences between desensitizing and non‐desensitizing nAChRs 7 . He has studied this target for many years while at several different industrial research facilities.…”
Section: Research Articlesmentioning
confidence: 99%